1995
DOI: 10.1136/jnnp.58.5.577
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multiple sclerosis in the region of Osona, Catalonia, northern Spain.

Abstract: To ascertain the prevalence of multiple sclerosis in the region of Osona in Catalonia, northern Spain, an intensive study was undertaken in a small population of 72 000 people over a period of five years, using many sources of information. Patients were classified according to the Poser criteria. Most of the patients presented with mild symptoms only and many had not seen a neurologist or attended a large hospital. The prevalence of definite and probable multiple sclerosis was 58 per 100 000. This is nine to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 15 publications
(7 reference statements)
5
36
1
2
Order By: Relevance
“…The results of our study, together with those obtained in other Spanish regions using a similar methodology [3,7,17,30], confirm our country as a high risk area for MS, with prevalence rates between 50 and 60 per 100,000. We believe that only a single further study in southern Spain is needed to confirm the survey findings of Fernández et al [6,7] in Málaga.…”
Section: Discussionsupporting
confidence: 89%
“…The results of our study, together with those obtained in other Spanish regions using a similar methodology [3,7,17,30], confirm our country as a high risk area for MS, with prevalence rates between 50 and 60 per 100,000. We believe that only a single further study in southern Spain is needed to confirm the survey findings of Fernández et al [6,7] in Málaga.…”
Section: Discussionsupporting
confidence: 89%
“…EDSS ölçeği hastanın özürlülük durumunu tespit etmek için kullanılan en pratik ve güvenilir ölçeklerden birisidir. Türkiye ve dünyadaki yapılmış çalışmalarda hastaların büyük çoğunluğunun EDSS skorlarının dü-şük olduğu bildirilmiştir [23][24][25] , bu verilerle uyumlu olarak bizim çalışmamızda da hastalardaki EDSS skorları 2'nin altında olan vaka sayısı yaklaşık %57 iken, 3'ün altındaki vaka yüzdesi %75'lere varmaktaydı.…”
Section: Materyal Ve Metot: çAlışmaya Dahil Edilen 210 Hastanın 126'sunclassified
“…It has been reported that the MS prevalence rates in Southern Europe are low-medium (2). However, it has also been shown that newly reported MS prevalence rates were higher than previously reported in Italy, Spain, Cyprus, and the Balkans (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 80%